If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8z + -10 = 6 Reorder the terms: -10 + 8z = 6 Solving -10 + 8z = 6 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 8z = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 8z = 6 + 10 8z = 6 + 10 Combine like terms: 6 + 10 = 16 8z = 16 Divide each side by '8'. z = 2 Simplifying z = 2
| 6(x-3)=5 | | 4.4y-4.9=4.9y-.04 | | 8-7y=2-y | | -14y+10=-14y-23 | | Y-2=7(x-3) | | 8z+3=6 | | 4v+2=2v-16 | | 2u-9=5u-3 | | 7.5y-2=17 | | 7x+5(2x-3)=9-7x | | .02z=z | | h(t)=-t^2+20t | | y^3=x+13 | | -.75z+.125=-.125-.08 | | 15.5=7v | | y=(4x^2+3)(5x^4-11) | | 8x+10-2x=13-14x-15 | | -4+n*2=0 | | Y-10=4(x-4) | | 10.1x+3.6=123.8 | | .17z+.5=-.5z-1 | | =16.25 | | y=(25x-3)(x^2-11) | | -4+n*2=12 | | -3x-2(9+5x)=17-2(2x-2) | | 4x-29=4x+2 | | 8x^2-3x-6=0 | | 2v+5=2v-4 | | -0.7x+0.5=-0.9-1.1x | | .15x+0.4(x-5)=.01(3x-3) | | 56p^7q+21p^6q^3+49p^4q^2=7p^4q | | -4x^2-31x-21=0 |